Tegoprazan dual and quadruple therapy for Helicobacter pylori eradication: a prospective, randomized controlled trial in Beijing, China - Cheng, Jianping; Zhao, Xiaolin; Fan, Chanjuan; Huang, Kun; Cai, Yong; Li, Zhen; Xie, Dongling; Zhai, Lili; Zhang, Xiaomei; Ding, Haiou (Frontiers in Medicine, 2025)
ObjectiveThe identification of novel and effective treatments for Helicobacter pylori (H. pylori) infection remains a critical need. Treatment is indicated for peptic ulcer disease, gastric MALT lymphoma, and gastric cancer prevention, following diagnosis via non-invasive testing or endoscopy. This study aimed to investigate the efficacy and safety of tegoprazan-based regimens compared to bismuth-containing quadruple therapy in H. pylori eradication.Patients and methodsIn a randomized, controlled, treatment-naïve adult patients with confirmed H. pylori infection were assigned in a 1:1:1 ratio to one of the following 14-day open-label therapies: BQT (rabeprazole 10 mg twice daily, compound bismuth aluminate granules 2.6 g thrice daily, amoxicillin 1 g twice daily, clarithromycin 500 mg twice daily), tegoprazan-based therapies (TAD, tegoprazan 50 mg twice daily, amoxicillin 1 g thrice daily; TBQT, tegoprazan 50 mg twice daily, compound bismuth aluminate granules 2.6 g thrice daily, amoxicillin 1 g twice daily, clarithromycin 500 mg twice daily). The primary outcome was the eradication rate of H. pylori. Secondary outcomes included the assessment of adverse events and treatment compliance.ResultsA total of 468 patients were enrolled. The eradication rates for TBQT, TAD and BQT were 86.3, 85.5 and 77.2%, respectively, by intention-to-treat analysis (p = 0.059), and 87.3, 87.2 and 77.7%, respectively, by per-protocol analysis (p = 0.029). The incidence of adverse events was comparable between the BQT and tegoprazan-based therapies (p > 0.05). Treatment compliance was similar across all three groups.ConclusionTegoprazan-based therapies achieved acceptable H. pylori eradication rates exceeding 85%, outperforming the BQT. Additionally, tegoprazan-amoxicillin dual therapy may serve as an alternative H. pylori eradication regimen in regions with high clarithromycin resistance.Clinical trial registrationhttp://clinicaltrials.gov, Identifier ChiCTR2300077088.